Harvesting of blooming microalgae using green synthetized magnetic maghemite (γ-Fe2O3) nanoparticles for biofuel production. (15th November 2019) - Duman, Fatih; Sahin, Ugur; Atabani, A.E.
Graphical abstract: Abstract: This study aims to harvest the hazardous algae from water using biologically synthetized magnetic nanomaterials with cheap, simple and environmentally friendly process to valorise it into biodiesel. The characteristics of obtained nanoparticles showed that it has 50 nm-sized hexagonal or round-shaped nanoparticles indicating its high adsorption capability due to its large surface area (78.4 m 2 g −1 ) and suitable porous volume (0.3 cm 3 g −1 ), and thus, proved to be effective to collect microalgae from water. The optimum conditions for harvesting efficiency (HE) were determined under a response surface methodology (RSM) using CCD approach (five-level, four-factor Central Composite Design) including various parameters; particle dosage, time, stirring speed and temperature while considering the HE (%) as the response. The optimized conditions for HE were found to be 56 mg L −1 particle dosage, 48 s, 310 rpm and 22.5 °C. The optimized algae HE was 82.4%. The lipid content of the harvested biomass was 5.6%. The produced oil was found to have high saturation level in which butyric (C4:0) (43.4%), heneicosanoic (C21:0) (22.4%), heptadecanoic (C17:0) (16.7%) and undecanoic (C11:0) (12.8%) acids were found as the dominant fatty acids. Fatty acid methyl esters (FAME) composition of obtained biodiesel was suitable comprising of 40.46% saturated fatty acids, 42.77% monounsaturated fatty acids and 16.77% polyunsaturated fatty acids. The physicochemical properties of the produced biodiesel were characterized. All properties, except acid value, satisfy international ASTM D6751 criteria and can be used commercially with acid neutralization.